2019
DOI: 10.5603/ocp.2019.0027
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic pain in oncology: cooperation between the oncologist and psychooncologist

Abstract: Treatment of chronic pain in oncology: cooperation between the oncologist and psychooncologist ABSTRACT The aim of this work is to present the problem of chronic pain in neoplastic disease as a situation requiring dia gnosis and interdisciplinary treatment. The phenomenon of chronic pain, its types, and causes are discussed.A discussion was held on appropriate scales for measuring pain intensity. Pharmacotherapy and psychotherapy were primarily presented among the discussed treatment methods, and issues relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 8 publications
(38 reference statements)
0
8
0
1
Order By: Relevance
“…That said, some women reported that they had made a journey of acceptance of the disease and its consequences, and the type of work performed is still the basis of acceptance and commitment therapy [ 18 ]. The cognitive changes in the way of seeing and perceiving pain following psychological support also demonstrate the validity of the theories underlying cognitive–behavioural therapy [ 28 ]. Likewise, cancer narration supporting sensemaking processes may bolster adaptation to the disease [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That said, some women reported that they had made a journey of acceptance of the disease and its consequences, and the type of work performed is still the basis of acceptance and commitment therapy [ 18 ]. The cognitive changes in the way of seeing and perceiving pain following psychological support also demonstrate the validity of the theories underlying cognitive–behavioural therapy [ 28 ]. Likewise, cancer narration supporting sensemaking processes may bolster adaptation to the disease [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of energy has been identified as the main cause of discomfort and as a motivation to avoid some of the most demanding activities [ 9 ]. Finally, a close relationship was shown between cognitive and emotional aspects and the perception of pain [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Psychotherapy is not only exotherapeutic but also endotherapeutic, because its effects influence the functioning of the central nervous system, as well as subordinate systems. Considering the situation of the oncological patient, it is not uncommon to depart from classical therapeutic methods in favour of alleviating symptoms, providing emotional and instrumental support, as well as motivating for treatment, open communication with the treatment team, or adherence to medical recommendations [3].…”
Section: Psychotherapeutic Methodsmentioning
confidence: 99%
“…• physical -associated with physiological symptoms, • functional -assessed on the basis of the patient's daily functioning and performance of self-service activities, • psychosocial -taking into account the impact of the pain experience on mental processes (mainly emotional) and the impact on the quality and quantity of relationships, • spiritual -related to life attitudes, the meaning of suffering, and the purpose of life, • behavioural -focusing on past experiences of pain, the current impact of pain on psychophysical conditions, and adaptation to cancer [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation